Unraveling the genomic diversity and ecological potential of the genus Demequina: insights from comparative analysis of different saline niche strains - Gao, Lei; Fang, Bao-Zhu; Lu, Chun-Yan; Hong, Kun-Hui; Huang, Xin-Yu; She, Ting-Ting; Xiao, Min; Li, Wen-Jun (Frontiers in Marine Science, 2023)
During an investigation of the culturable microbial diversity of sediments with salinity from tidal flats and saline lake, seven strains of the genus Demequina were harvested. The genomic analysis and physiological characteristics of strains of this genus have unveiled their significant potential in degrading complex carbon source such as lignin, hemicellulose, chitin, and oligosaccharides. In addition, these strains show potential abilities in nitrite ammonification and sulfide oxidation. These findings not only improved our understanding of their metabolic model, but also provided valuable insights into their ecological roles. Four new species of the genus Demequina are described: Demequina litoralis sp. nov., with SYSU T00192T designated as the type species; Demequina zhanjiangensis sp. nov., with SYSU T00b26T as the type species; Demequina lignilytica sp. nov., with SYSU T00068T as the type species; and Demequina muriae sp. nov., with EGI L300058T as the type species. Additionally, strains SYSU T0a273, SYSU T00039-1, and SYSU T00039 are identified as different strains of Demequina lignilytica. Our study thus sheds light on the diversity, biological significance, and ecological contribution of the Demequina genus in different habitats.